Solution concepts of principal-agent models with unawareness of actions - Ying-ju Chen; Xiaojian Zhao (Games, 2013)
In numerous economic scenarios, contracting parties may not have a clear picture of all the relevant aspects. A contracting party may be unaware of what she and/or others are entitled to determine. Therefore, she may reject a contract that is too good to be true. Further, a contracting party may actively exert cognitive effort before signing a contract, so as to avoid being trapped into the contractual agreement ex post. In this paper, we propose a general framework to investigate these strategic interactions with unawareness, reasoning and cognition and intend to unify the solution concepts in the contracting context with unawareness. We build our conceptual framework upon the classical principal-agent relationship and compare the behaviors under various degrees of the unaware agent's sophistication.
Keywords: 330; unawareness; cognition; incomplete contracts; principal-agent relationship